2002
DOI: 10.1186/cc1831
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: IntroductionThere are numerous randomized, controlled trials and several meta-analyses evaluating drug therapy for stress ulcer prophylaxis [1]. While these publications have shown significant benefit with using prophylaxis, a number of issues still remain unresolved. For example, Cook et al. performed a meta-analysis of published and unpublished research, and they concluded that sucralfate might be as effective as pH-altering medication in preventing stress-induced bleeding, with a lower incidence of pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 21 publications
(24 reference statements)
2
6
0
Order By: Relevance
“…Notably, this population, often under-represented in literature, demonstrated a higher SUP utilization rate compared with previous studies, but a lower rate than others (75–95%). 11 16 19 H2RAs were predominantly prescribed (88%) over PPIs (12%), potentially due to cost-effectiveness and the associated lower risk of infections, aligning with findings reported in the literature. 5 21 Additionally, this study found a low incidence of CSGIBs (1%) in this high-risk patient population, which is consistent with the rate reported by Palm and colleagues of 0.7% in patients with TBI with enteral feeding and lower than the rate reported previously for general critically ill patients.…”
Section: Discussionsupporting
confidence: 84%
“…Notably, this population, often under-represented in literature, demonstrated a higher SUP utilization rate compared with previous studies, but a lower rate than others (75–95%). 11 16 19 H2RAs were predominantly prescribed (88%) over PPIs (12%), potentially due to cost-effectiveness and the associated lower risk of infections, aligning with findings reported in the literature. 5 21 Additionally, this study found a low incidence of CSGIBs (1%) in this high-risk patient population, which is consistent with the rate reported by Palm and colleagues of 0.7% in patients with TBI with enteral feeding and lower than the rate reported previously for general critically ill patients.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, drug selection for SUP was determined by the H2RA class and the PPI class was the second choice, which is consistent with survey findings among Canadian (2) and United States (23) prescribers. In contrast, results of the studies by Vazin et al (20) and Shahbazi et al (24) in Iran, by Horsa et al (7) in Ethiopia and by Chen et al (25) in the United States, revealed that intravenous pantoprazole was the most prescribed drug for SUP.…”
Section: Discussionsupporting
confidence: 73%
“…This is reflected in the recent North American cross-sectional observational study mentioned above where PPIs were administered intravenously in 46% of patient-days. 8 We therefore elected to evaluate intravenous PPI to ensure that all patients could receive prescribed doses each day. Furthermore, using only the intravenous route minimizes the possibility of administration errors or missed doses which are more likely when switching between intravenous to enteral routes.…”
Section: Discussionmentioning
confidence: 99%
“… 10 – 12 For instance, a 58-center Canadian and American observational study confirmed that PPIs are used for SUP in 70% of patients receiving SUP in the ICU. 8 This may reflect the lower risk of clinically important bleeding with PPIs over H2RAs. 13 , 14 …”
mentioning
confidence: 99%